2010
DOI: 10.1186/ar3029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and serological evaluation of a novel CENP-A peptide based ELISA

Abstract: IntroductionAnti-centromere antibodies (ACA) are useful biomarkers in the diagnosis of systemic sclerosis (SSc). ACA are found in 20 to 40% of SSc patients and, albeit with lower prevalence, in patients with other systemic autoimmune rheumatic diseases. Historically, ACA were detected by indirect immunofluorescence (IIF) on HEp-2 cells and confirmed by immunoassays using recombinant CENP-B. The objective of this study was to evaluate a novel CENP-A peptide ELISA.MethodsSera collected from SSc patients (n = 334… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
3
14
1
Order By: Relevance
“…Altogether, these results strongly suggest that CENP-A Abs are generated independently from anti-CENP-B Abs and that the previously reported motif G/APXRX is not responsible for any cross-reactivity between anti-CENP-A and -CENP-B Abs [18], [32]. Supporting this conclusion are the results by Mahler et al [33], who reported a lack of cross-inhibition between anti-CENP-A and anti-CENP-B Abs, using an amino terminal CENP-A-derived peptide (sequence not reported) and recombinant CENP-B as inhibitor.…”
Section: Discussionsupporting
confidence: 77%
“…Altogether, these results strongly suggest that CENP-A Abs are generated independently from anti-CENP-B Abs and that the previously reported motif G/APXRX is not responsible for any cross-reactivity between anti-CENP-A and -CENP-B Abs [18], [32]. Supporting this conclusion are the results by Mahler et al [33], who reported a lack of cross-inhibition between anti-CENP-A and anti-CENP-B Abs, using an amino terminal CENP-A-derived peptide (sequence not reported) and recombinant CENP-B as inhibitor.…”
Section: Discussionsupporting
confidence: 77%
“…In a previous study dcSSc and lcSSc subsets were associated with particular organ manifestations, but in this analysis the clinical distinction appeared superseded by an antibody-based classification in predicting some SSc-related complications [33]. In addition, the discrimination between SSc and controls as measured by the AUC (0.73) derived from ROC analysis using anti-Th/To (Rpp25) antibody results was similar to the AUC (0.67) generated by ACA [34]. …”
Section: Discussionsupporting
confidence: 54%
“…The CENP-A ELISA (Dr. Fooke Laboratorien GmbH), a CE-certified peptide-based assay, was performed according to the manufacturer's instructions as described 14 . The CENP-A ELISA (Dr. Fooke Laboratorien GmbH), a CE-certified peptide-based assay, was performed according to the manufacturer's instructions as described 14 .…”
Section: Methodsmentioning
confidence: 99%
“…While a few studies have examined the prevalence of CENP-A and -B in SSc 14,15 , little has been published on the clinical correlates of the individual CENP-A or CENP-B autoantibodies. While a few studies have examined the prevalence of CENP-A and -B in SSc 14,15 , little has been published on the clinical correlates of the individual CENP-A or CENP-B autoantibodies.…”
mentioning
confidence: 99%